Relationship between serum lipid level and colorectal cancer: a systemic review and meta-analysis - Shuai Lu; Zhenpeng Yang; Huazhen Tang; Xibo Sun; Benqiang Rao (BMJ Open)
Objective Investigative studies report contradictory results of the relationship between serum lipid levels and the risk of colorectal cancer (CRC). We conducted a meta-analysis of prospective published studies to clarify the relationship between serum lipid and CRC risk.Design Systematic review and meta-analysis.Data Sources PubMed and Embase from inception until December 2020.Eligibility criteria We considered prospective cohort and case–control studies that evaluated differences in serum lipid levels with the risk of developing CRC.Data extraction and synthesis Two independent reviewers screened and included the studies using standardised electronic data extraction forms. The relative risks of the studies were combined with random-effect and fixed-effect models and were analysed for heterogeneity, publication bias and sensitivity.Results Twenty-four prospective studies, including 4 224 317 individuals with 29 499 CRC cases, were included in the meta-analysis. The total pooled risk ratio (RR) for high vs low concentrations of triglyceride (TG) concentrations was reported at 1.21 (95% CI 1.09 to 1.34; I2=46.8%), total cholesterol (TC) was at 1.15 (95% CI 1.08 to 1.22; I2=36.8%), high-density lipoprotein cholesterol (HDL-C) was 0.86 (95% CI 0.77 to 0.97; I2=28.8%) and low-density lipoprotein cholesterol (LDL-C) was observed at 1.03 (95% CI 0.75 to 1.41; I2=69.4%).Conclusions This meta-analysis shows that high levels of serum TG and TC are positively correlated with the incidence rate of CRC, while high levels of serum HDL-C are negatively correlated with CRC incidence rate. Furthermore, no association was found between LDL-C and the risk of developing CRC. Nevertheless, the heterogeneity brought about by comparative methods, demographic differences and pathological differences between the research subjects limits the effectiveness of the overall pooled results.